THE INFLUENCE OF SERVICE QUALITY AND PHYSICAL EVIDENCE ON REVISIT INTENTION: A LITERATURE REVIEW - Dwi Wahyu Rusdianita; Mirrah Samiyah; Ansarul Fahrudda (Yayasan Nuraini Ibrahim Mandiri, 2025)
This literature review aims to examine the influence of service quality and physical evidence on revisit intention in healthcare settings. As patient loyalty becomes increasingly critical in competitive health service markets, understanding non-medical service factors is essential. This review systematically analyzes 20 empirical journal articles published between 2016 and 2024, focusing on how tangible environmental elements and frontline service delivery affect patients' likelihood of returning to the same healthcare facility. Data were collected from journal databases using keywords such as